Desempenho de falantes do português brasileiro no “Test of Narrative Language (TNL)” - Costa, Gabriela Mello [UNESP]; Rossi, Natalia Freitas [UNESP]; Giacheti, Célia Maria [UNESP] (FapUNIFESP (SciELO), 2018)
PURPOSE: Investigate the performance of native speakers of Brazilian Portuguese in the Test of Narrative Language (TNL) and correlate their performance in its oral narration and narrative comprehension subtests. METHODS: Participants were 140 individuals with typical language development aged 5-0 to 11-11 (years-months) divided according to age group. RESULTS: Statistically significant difference was observed between the 5-year-old group and all the other age groups and between the 6-year-old group and the 8-, 9-, 10- and 11-year-old groups. The 7-year-old group did not differ from the 6- and 8-year-old groups. Half of the 7-year-old group was in 1st grade of Elementary School and the other half was in 2nd grade, which may have contributed to the non-differentiation between this group and its border-age groups. No statistically significant difference was found between groups as of the age of eight years. Positive correlation was observed between performance in the narrative comprehension and oral narration subtests of the TNL in the 5-, 6- and 7-year-old groups, which did not occur for the other age groups. CONCLUSION: The Test of Narrative Language differentiated the 5-, 6- and 7-year-old groups, but did not differentiate groups as of the age of eight years. No correlation was found between performance in the oral narration and narrative comprehension subtests of the TNL as of the age of eight years, which suggests mastery of both skills from this age.

OBJETIVO: Investigar o desempenho de falantes do português brasileiro no Test of Narrative Language e correlacionar o desempenho nas tarefas de produção e compreensão da narrativa. MÉTODO: Participaram 140 indivíduos, entre 5 e 11 anos e 11 meses de idade com desenvolvimento típico de linguagem, divididos de acordo com a faixa etária. RESULTADOS: Diferença significativa foi encontrada entre o grupo de 5 anos e todos os demais grupos etários, bem como para o grupo de 6 anos quando comparado ao grupo de 8, 9, 10 e 11 anos. O grupo de 7 anos não diferiu estatisticamente dos grupos de 6 e 8 anos. Metade do grupo de 7 anos cursava o primeiro ano e a outra metade, o segundo ano, o que pode ter contribuído para a não diferenciação do grupo com as faixas etárias fronteiriças. Não foi encontrada diferença estatisticamente significante entre os grupos a partir dos 8 anos. Observou-se correlação positiva entre o desempenho de compreensão e produção nos grupos etários de 5, 6 e 7 anos, o que não ocorreu para os demais grupos. CONCLUSÃO: O teste diferenciou as faixas etárias de 5, 6 e 7 anos, o que não ocorreu nas faixas etárias a partir dos 8 anos. Também, a partir dos 8 anos, não foi encontrada correlação entre a produção e a compreensão narrativa, sinalizando o domínio de ambas as habilidades a partir desta faixa etária.
Performance of Brazilian Portuguese speakers in the Test of Narrative Language (TNL)